A new species of Lycidioides Ando (Coleoptera, Tenebrionidae, Stenochiinae) from the Malay Peninsula, with the first record of the genus outside Borneo - Hanai, Makito; Ando, Kiyoshi; Maruyama, Munetoshi; Hazmi, Izfa Riza (Zootaxa, 2026)
A new species of the tenebrionid genus Lycidioides Ando, 2003, L. cheongi sp. nov., is described from the Malay Peninsula (Malaysia). This study reports the first record of the genus in the Malay Peninsula, representing the first record of the genus outside Borneo. A key to known species of the genus is also provided. Additionally, the phylogenetic position of the genus is inferred from the morphology of defensive glands, and its potential as a useful material for future biogeographical research is also discussed.